Qualidade da água superficial em microbacias com diferentes usos de solo no município de Itaara - RS - Oliveira, Josiéle Madeira de (2013)
This work was developed with the main objective to analyze the water quality in watersheds with different uses and land use in the municipality of Itaara - RS . The municipality characteristics of rural and urban use, and due to great concern in recent years with the problems of scarcity of natural resources, especially water resources opted for this approach that could be contributing in discussions that relate to environmental issues to achieve the objectives, firstly, the basin was delimited included in the study. Through the use of geoprocessing tools developed to map land use from satellite images CBERS 2B, bands 2 , 3, 4 and 5, from December 21, 2008, which was the identification of five classes: bodies water, urban area , field, forest and bare soil . After delimited sampling sites were established four collection points distributed in areas with different soil where some variables were analyzed the physical conditions and chemical and microbiological water as dissolved oxygen pH, Electrical Conductivity and water temperature, total dissolved solids and total coliforms and Escherichia coli. From the analysis of the map and use cover and the results of the parameters observed the influence of the uses on water quality, however the concentrations were within the limits established on the basis of Resolution 357 of 2005 of the National Council the Environment (CONAMA ).